Euthanasia in Malaysia / Elsa Baharum … [et al.] - Baharum, Elsa; A.M. Ibnu, Faezahwaty; Mehdi Bakavoli, Annahita Bakavoli (Faculty of Law, 2005)
The legalisation of euthanasia has always been a debatable issue amongst different groups in our country. Due to the fact that euthanasia is still illegal in our country, several problems arise where euthanasia is concerned when the practice of medical practitioners in assisting their patient's death comes into light. The main aim of this research paper is to study Malaysia's position on euthanasia and whether or not it should be legalised. During the course of this study, several relevant and reliable sources will be referred to. These sources include legal materials such as statutes, case laws, law reports and books. Other sources of information include newspaper articles, guidelines on medical ethics, and also ideas and suggestions that arose from conferences on euthanasia in Malaysia. Interviews will be conducted with both legal and medical practitioners as well as academicians that have expertise in this field. It is hoped that at the end of this study, a better understanding of Malaysia's position on euthanasia could be gained to start the momentum for passive voluntary euthanasia to be legalised if certain requirements are fulfilled. The practice carried out in the hospitals of other jurisdictions will be analysed to find out if such practice is suitable to local circumstances for legalising it. We would also like to put forth our proposition that the practice of passive voluntary euthanasia should be legalised for the sake of terminally ill patients who wish to die in dignity and to end their pain and sufferings.